Pengaruh Literasi terhadap Kecerdasan Emosional Anak Usia 5 Hingga 10 Tahun - Faris Jihadi Hanifa; Davina Nur Hidayah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article contains an analysis of emotional intelligence in children aged 5 to 10 years, this study aims to find out more about the development of children in their emotional intelligence, which is also related to literacy. Because literacy is an influence on hearing, understanding children's thoughts, and it will affect their emotional intelligence. And the problems in the influence of literacy on children's emotional intelligence include difficulties in controlling emotions, the impact of the social and cultural environment, and limitations in understanding literacy that can hinder emotional development. In addition, the lack of support from parents is also a significant factor. This study uses qualitative methods that can allow researchers to explore children's experiences, views, and feelings in depth. In the context of literacy and emotional intelligence, researchers can find out how children feel and interpret their emotions and how literacy plays a role in the process. Through reading and discussing emotions, children can improve their understanding of themselves and others, develop empathy, and improve communication skills and emotional management. By integrating literacy and emotional intelligence into education and everyday life, we can help children develop the skills needed to interact positively and manage their emotions effectively.